2014
DOI: 10.1038/nrendo.2014.11
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility to type 2 diabetes mellitus—from genes to prevention

Abstract: Knowledge of the genetics of type 2 diabetes mellitus (T2DM) has evolved tremendously over the past few years. Following advances in technology and analytical approaches, collaborative case–control genome-wide association studies have revealed up to 65 loci credibly associated with T2DM. Prospective population studies have demonstrated that aggregated genetic risk scores, so-called because they sum the genetic risk attributed to each locus, can predict incident T2DM among individuals of various age ranges and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0
8

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(50 citation statements)
references
References 59 publications
(82 reference statements)
0
42
0
8
Order By: Relevance
“…We used an unweighted GRS for non-European ancestry cohorts because most of the T2D SNPs come from GWAS conducted among people of European ancestry. However, weighting has little effect on the GRS 35 , makes models fit slightly better, but does not change the ranking of individuals from low to high risk 15, 35 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We used an unweighted GRS for non-European ancestry cohorts because most of the T2D SNPs come from GWAS conducted among people of European ancestry. However, weighting has little effect on the GRS 35 , makes models fit slightly better, but does not change the ranking of individuals from low to high risk 15, 35 .…”
Section: Methodsmentioning
confidence: 99%
“…We have also shown that an additive genetic risk score (GRS 62 ) comprised of 62 validated T2D-associated SNPs 11-14 predicts incident T2D in European and African Americans 15, 16 .…”
Section: Introductionmentioning
confidence: 94%
“…Epigenetik deği-şimlerin de T2DM ve onun fenotipik özellikleriyle ilişkili olduğuna dair kanıtların olması, bu alanda da yapılacak araştırmalara ihtiyaç olduğunu ve T2DM tahmini ile ilgili katkı sunabileceğini göstermektedir (124,128,129). (149). Yakın zamanda yapılan bir çalışma, pek çok T2DM lokusunun glukoz homeostazisi üzerindeki potansiyel bozucu etkisinin, yüksek fiziksel aktivite ya da sağlıklı yaşam tarzı davranışları ile ortadan kaldırılabildiğini ya da en azından hafifletilebildiğini veya tam tersi düşük fiziksel aktivite ve batı tarzı diyet faktörle-rinin bu bozucu etkiyi daha da artırabildiğini göstermiş-tir (89).…”
Section: Aday Gen Yaklaşımıunclassified
“…The PPARG gene is implicated in adipogenesis and the development of insulin resistance. Deleterious mutations in this gene impair insulin resistance and can cause lack of response to insulin 23 . From recent genome-wide association .…”
Section: Role Of Genetics In the Development Of Type 2 Diabetes Mellitusmentioning
confidence: 99%